Trends in nursing burnout management in foreign studies (literature review) - A. D. Golmenko; V. A. Khaptanova; V. P. Peskov; A. Yu. Khaptanov (Acta Biomedica Scientifica, 2021)
This review provides a general foreign overview of the current understanding and  prevalence of professional burnout among medical workers and summarizes the emerging trends in the management of the organization of work of nurses, preventing burnout, and an analysis of practices aimed at preventing burnout. Burnout negatively affects both mental and physical health, as well as increases economic losses and employee turnover.Burnout depends on factors such as job satisfaction, professional rank, hospital level, gender, professional values, negative emotions, and core competencies.Burnout syndrome is closely related to compassion fatigue syndrome, compassionate gratification and is part of the broader concept of professional quality of life. Compassion refers to recognition, understanding, emotional resonance, empathic concern and tolerance for the suffering of others, and motivation and action in relationships to help others.The analysis of foreign literature has shown the relevance of this problem and, first of all, for nurses. The peculiarities of the work of nurses lead to the fact that their burnout is higher than among other medical workers. Various approaches to the management of professional burnout have been proposed. Burnout management can focus on the organization, the individual, or a combination of interventions.When people have a positive belief system, work involvement, and access to many personal resources, they are less likely to experience stress and burnout.Nursing burnout has worsened during the COVID-19 period and has exposed new pressing health issues. The COVID-19 pandemic has shown a shortage of nurses and has become a major problem in many countries.The attitude of the community, the importance and the need for specialized and professional care, especially in situations of great difficulty and suffering, is important for medical personnel. Public sincere gratitude for the work of healthcare professionals will help build compassion for professionals who risk their lives to help people.